2022
DOI: 10.1161/atvbaha.122.317670
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Siphon Calcification Predicts the Symptomatic Progression in Branch Artery Disease With Intracranial Artery Stenosis—Brief Report

Abstract: Background: Arterial calcification in the aortic arch, carotid bifurcation, or siphon on computed tomography was associated with cardiovascular disease. The association between arterial calcification prevalence and progression of branch atheromatous disease (BAD) in intracranial artery atherosclerosis was little investigated. Methods: This study included 310 patients with ischemic stroke from one stroke center. Patients were divided into BAD (110) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
3
1
Order By: Relevance
“…Second, participants in this study were stroke patients, while those in Spanish study were healthy physical examiners. Previous studies indicated that carotid calcification was associated with atherosclerotic cardiovascular diseases, including ischemic stroke [4]. Third, dairy total flavonoid intake was lower in this study than that in Spanish study (183 ± 234 vs. 546 ± 264 mg/d).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Second, participants in this study were stroke patients, while those in Spanish study were healthy physical examiners. Previous studies indicated that carotid calcification was associated with atherosclerotic cardiovascular diseases, including ischemic stroke [4]. Third, dairy total flavonoid intake was lower in this study than that in Spanish study (183 ± 234 vs. 546 ± 264 mg/d).…”
Section: Discussioncontrasting
confidence: 66%
“…Intracranial artery calcification was also associated with increased risk of hemorrhage and decreased likelihood of favorable outcome after intravenous thrombolysis in patients with acute non-cardioembolic ischemic stroke [3]. Carotid siphon calcification could predict the symptomatic progression in branch artery disease with intracranial artery stenosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Calcification in the pre-cranial arteries, which include aortic arch calcification (AoAC) and carotid siphon calcification (CaSC), is associated with the burden of systemic calcification. 8 Kim et al. found that calcifications of the internal carotid artery (ICA) can reflect the degree of cerebral atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Calcification in the pre-cranial arteries, which include aortic arch calcification (AoAC) and carotid siphon calcification (CaSC), is associated with the burden of systemic calcification. 8 Kim et al found that calcifications of the internal carotid artery (ICA) can reflect the degree of cerebral atherosclerosis. 9 Because the aortic arch to the carotid artery is the only way for intravenous recombinant tissue plasminogen activator (rt-PA) or thrombectomy devices to enter the brain, we hypothesized that assessment of the calcification burden of AoAC and CaSC may be a factor in predicting the outcomes of reperfusion therapy.…”
Section: Introductionmentioning
confidence: 99%